The New Age Urban Transportation Systems : Cases from Asian Economies. - Narayanaswami, Sundaravalli (Business Expert Press, 2019)
Urbanization is a global phenomenon that hugely constrains existing transportation infrastructure in cities. Urban transportation (UT) challenges are more significant in developing countries with rapid development as the land occupation is dense. Limited urban space and infrastructure fail to meet the increasing traffic demands and to provide reasonable service quality. Therefore betterment of UT systems is more required than ever.